Service Quality and Costume Satisraction in Convection Businesses - Anggia Arif; Fanny Lim (ARRUS Journal of Social Sciences and Humanities, 2023)
This study is to determine whether service quality and customer satisfaction in Convection Business. The research method used is associative quantitative research. The following research sample on service and customer satisfaction in the convection business amounted to 97 respondents. Sampling using accidental sampling technique. Data analysis using simple linear regression test and correlation coefficient. The results showed that there was an effect of service quality on customer satisfaction of 11.2%.